THE STATE OF ANTIOXIDANT SYSTEM OF THE WOMEN UNDERGOING THE PROCEDURE OF IN VITRO FERTILIZATION - M. Yu. Prorubschikova; L. I. Kolesnikova; L. V. Suturina (Acta Biomedica Scientifica, 2012)
The antioxidant system activity was studied in 74 patients undergoing infertility treatment by the vitro fertilization, depending on the effectiveness of the procedure.